Screens and brains: multimodal neuroimaging insights into mechanisms of problematic smartphone use - Wolf, Nadine D.; Henemann, Gudrun Maria; Schmitgen, Mike; Koenig, Julian; Bach, Patrick; Wolf, Robert Christian (Progress in neuro-psychopharmacology & biological psychiatry, 2025)
Background - Problematic smartphone use (PSU) is increasingly regarded as a form of behavioral addiction, marked by compulsive engagement and diminished self-regulation. An expanding body of evidence points to distinct neural correlates of PSU, including heightened sensitivity to smartphone-related cues, aberrant reward processing, and executive dysfunction. - Objectives - This systematic review synthesizes contemporary evidence from multimodal neuroimaging studies that seek to elucidate the neurobiological substrates of PSU. To unify and contextualize these findings, a social-cognitive framework is proposed. - Methods - A pre-registered systematic literature review (PROSPERO ID no. 1068662) was conducted to identify structural and functional neuroimaging studies on problematic smartphone use (PSU) published in the past decade. - Results - Neuroimaging data consistently demonstrate abnormalities in frontostriatal and frontolimbic circuits, implicating reduced executive control, heightened cue reactivity, and altered processing of socially salient stimuli. Neural responses to smartphone-related reward cues exhibit substantial convergence with activation patterns associated with social cognition. Social-cognitive distortions, such as maladaptive interpretations of digital social feedback, may potentiate the motivational salience of smartphone cues, thereby reinforcing compulsive usage patterns. - Conclusion - Reviewed studies indicate that PSU emerges from a dynamic and multifactorial interaction between neurobiological vulnerabilities, affective responsiveness, cognitive biases, and impairments in executive control. These factors show patterns of reciprocal reinforcement, facilitating the consolidation of automatic, habitual engagement with smartphone-mediated stimuli. Within this framework, socially mediated reinforcement mechanisms may serve as critical drivers for both, the development and persistence of PSU. Integration of social-cognitive factors of PSU offers promising avenues for future prevention and intervention strategies, highlighting targets for future investigations.